2022
DOI: 10.1590/2317-1545v44263126
|View full text |Cite
|
Sign up to set email alerts
|

Wheat seed germination based on α-amylase activity to study promoting mechanism of Bacillus subtilis QM3

Abstract: The mechanism of promoting wheat seed germination by Bacillus subtilis has been paid great attention by many scholars. The germination rate and α-amylase activity of wheat seeds were significantly increased after germinating with Bacillus subtilis QM3 in this paper. Inhibitor and promoter of α-amylase were used to study relationship between bacteria and α-amylase. Compared with inhibitor group (10 mmol.L-1 EDTA), α-amylase activity of seeds treated by B. subtilis QM3 (106 CFU.mL-1) increased by 19.8%. It indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Wheat seeds are rich in starch, and starch absorption and reuse during seed germination are associated with amylase activity. The aging of wheat seeds decreases the activity of amylase, and amylase activities are directly related to seed germination rate [71][72][73]. In the present experiment, aging led to the decline of amylase activity, and the decline under natural aging was significantly less than that under artificial aging, which indicated that the amylase decline was associated with the severity of aging.…”
Section: Discussionmentioning
confidence: 58%
“…Wheat seeds are rich in starch, and starch absorption and reuse during seed germination are associated with amylase activity. The aging of wheat seeds decreases the activity of amylase, and amylase activities are directly related to seed germination rate [71][72][73]. In the present experiment, aging led to the decline of amylase activity, and the decline under natural aging was significantly less than that under artificial aging, which indicated that the amylase decline was associated with the severity of aging.…”
Section: Discussionmentioning
confidence: 58%
“…This study evaluated the release of seed dormancy by measuring the nutrient transformation in seeds. α-Amylases play a crucial role in converting nutrients [44]. GA 3 influences the production of a-Amylases to control the amount of some nutrients [45].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, several Bacillus spp. increase the germination rate of tomato seed (Patani et al, 2023), while Bacillus subtilis increases wheat seed germination through stimulation of α‐ and β‐amylase activities (Hu et al, 2022). Moreover, several strains not only combine PGPR and disease tolerance (Mehmood et al, 2023), but some strains also show plant protective properties under abiotic stresses (Xia et al, 2020; Sarker et al, 2021; Naing et al, 2021; El‐Saadony et al, 2022).…”
Section: Introductionmentioning
confidence: 99%